Implementation Of Children's Manners To Parents In Islamic Religious Education At Junior High School Level - Lukman Nol Hakim; E. Mujahidin; Budi Handrianto (International Journal of Education, Vocational and Social Science, 2024)
The degeneration of manners, the first to be highlighted are junior high school students because it is concerning. In an effort to increase understanding of the importance of adab. Some schools have already instilled the material of adab children to parents. However, not explicitly. The adab shown by children to their parents is not significant. The formulation of the problems in this study are 1. how is the learning of manners in Islamic religious education in the first high school of State 18 Bogor? How is the concept of children's manners to parents ideal for the junior high school level? While the objectives are 1. want to analyze how the learning of manners in Islamic religious education in junior high school Negeri 18 Bogor. 3. want to formulate the concept of children's manners to parents who are ideal for junior high school level. This research approach is qualitative with the type of field study. Data sources are taken from; a. primary, namely; primary data sources in the field study through structured interviews with Islamic Religious Education teachers at State Junior High School 18 Bogor. b. secondary, namely; field study data looking at the 2013 curriculum Islamic Religious Education material. The results of Islamic Religious Education Learning at the State Junior High School 18 Bogor refer to lesson plans and habituation through motivation about children's manners to parents, teachers and friends, reading the Qur'an, praying dhuha before teaching and learning activities begin and at the end of each year students are asked to write and reflect on the goodness of their respective parents. In terms of material, the adab of children to parents needs improvement. The ideal concept of children's manners to parents in junior high school is to have a goal of graduating with good Islamic character, morals and spirituality. The content of the program is more practical. The method is more practical, in terms of evaluation making adab as a graduation requirement at the junior high school level.